2004
DOI: 10.1038/sj.leu.2403244
|View full text |Cite
|
Sign up to set email alerts
|

Studies in NZB IL-10 knockout mice of the requirement of IL-10 for progression of B-cell lymphoma

Abstract: NZB mice develop an age-related malignant expansion of a subset of B cells, B-1 cells, with autocrine production of IL-10. IL-10, a pleiotropic cytokine with anti-inflammatory properties, is a potent growth and survival factor for malignant B cells. To further examine the in vivo requirement for IL-10 in the development and expansion of malignant B-1 clones in NZB mice, we developed a strain of homozygous IL-10 knockout (KO) mice on an NZB background. The NZB IL-10 KO mice develop peritoneal B-1 cells with app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 36 publications
4
41
0
Order By: Relevance
“…In this regard, Ramachandra and coworkers (Ramachandra et al, 1996) demonstrated that high interleukin (IL)-10 levels in NZB mice were correlated with B-1 cell transformation. In agreement with a role for IL-10 in CLL development in this mouse model, IL-10 depletion achieved either by targeting deletion of the IL-10 gene (Czarneski et al, 2004) or by in vivo administration of antisense IL-10 (Parker et al, 2000;Peng et al, 1995) delayed, and even prevented, CLL development. IL-5 is another member of the IL family that seems to play an important role as a switch for SLE or CLL development.…”
Section: Nzb Mice In the Crossroad Of Autoimmunity And Cllsupporting
confidence: 84%
“…In this regard, Ramachandra and coworkers (Ramachandra et al, 1996) demonstrated that high interleukin (IL)-10 levels in NZB mice were correlated with B-1 cell transformation. In agreement with a role for IL-10 in CLL development in this mouse model, IL-10 depletion achieved either by targeting deletion of the IL-10 gene (Czarneski et al, 2004) or by in vivo administration of antisense IL-10 (Parker et al, 2000;Peng et al, 1995) delayed, and even prevented, CLL development. IL-5 is another member of the IL family that seems to play an important role as a switch for SLE or CLL development.…”
Section: Nzb Mice In the Crossroad Of Autoimmunity And Cllsupporting
confidence: 84%
“…Treatment with z-VRPRfmk for 36 hours and more also led to a predominant reduction in the transcription and expression of IL-10 ( Fig. 3D), which can promote the growth of activated B cells and B-cell lymphomas (20)(21)(22). The observed reduction of IL-6 and IL-10 cytokine levels in VRPR-fmk treated ABC DLBCL lines correlated with a decrease in the expression of these genes in two ABC DLBCL lines treated with the MALT1 inhibitor (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…21 Mouse B-cell lymphomas that arise spontaneously in the New Zealand Black strain produce IL-10, and IL-10 is required for their generation. 22 IL-6 and IL-10 are secreted by malignant cells purified from some patients with non-Hodgkin lymphoma (NHL), and this phenotype correlates with circulating levels of the corresponding cytokines in serum. 23 Binding of IL-6 and IL-10 to their surface receptors activates JAK family kinases, initiating several cascades of intracellular signaling events.…”
Section: Introductionmentioning
confidence: 99%